Readiness To Quit Addiction! A Study Among Patients Attending Tertiary Care Hospital in Western India - Pandya, Chandresh M; Mehta, Kedar G; Solanki, Dipak M (National Journal of Community Medicine, 2015)
Introduction: Tobacco use has been an important public health prob- lem in India. Information related to addiction habits among patients visiting GMERS Gotri General Hospital is scarce. Hence, it is neces- sary to know these habits and patients’ readiness to quit for streng- thening de-addiction services in this set up. Methodology: A cross sectional study was conducted among outpa- tients of GMERS Gotri Hospital from 30th May - 6th June 2015 using a pretested semistructured questionnaire. Data was entered and ana- lysed using Epi Info Software. Results: Out of 626 addictive patients registered, half of them were in the middle age group and from rural areas. The most common form of addiction was tobacco chewing (66.4%) followed by smoking (32.7%) and alcohol (19.4%). 68.4% of these patients showed readi- ness to quit. Conclusion: Moreover, majority of patients were ready to quit addic- tion, so there is a need to strengthen the available de-addiction ser- vices in this tertiary care hospital.